Molecular and morphological data support the synonymy of Muricanthus radix Gmelin, 1791 and Muricanthus ambiguus Reeve, 1845 (Gastropoda, Muricidae) - Francisco Morinha; James Ernest; Ana Archer-Taveira; Ana M. Rocha; Robert T. Iwamasa (ZooKeys)
The Muricanthus radix/ambiguus/nigritus complex includes species with a great diversity of shell shapes and shared habitats in various regions, which has raised questions and doubts about the current taxonomic classification of these species. Muricanthus nigritus, M. radix, and M. ambiguus are three similar-looking black and white murex found commonly on the west coast of North and South America. The wide variety of morphological patterns within and between these species makes the classification of specimens difficult by visual observation. To this day, controversy persists over whether M. radix and M. ambiguus are one or two distinct species. Molecular genetic data have helped clarify the taxonomic classification of many mollusk species in recent decades, contributing to a more accurate understanding of biodiversity and ecosystems. In this study, DNA barcoding and double digest restriction-site associated DNA sequencing (ddRAD-seq) methodologies were applied to complement morphological data, establishing for the first time the phylogenetic relationships between M. nigritus, M. ambiguus and M. radix. The classic mitochondrial and nuclear barcodes obtained from 80 specimens collected from three different geographic locations differentiated only two phylogenetic clades (M. nigritus and M. radix/ambiguus from Mexico differentiated from M. radix/ambiguus from Mexico and Panama). High levels of mitochondrial DNA introgression have been observed between M. nigritus and M. radix/ambiguus. The deep-level approach performed using 3692 loci obtained from ddRAD-seq also differentiated only two genetic clusters (M. nigritus and M. radix/ambiguus). Our results clearly support the proposal that M. ambiguus should be synonymized with M. radix.